Evaluation of Las Working Practice in Study Program D III Mechanical Engineering FT UNJ - Dudung, Agus (International Journal of Psychosocial Rehabilitation, 2020)
The evaluation of this process aims to: obtain data on students' opinions about weaknesses in the management of the learning process teaching welding practice courses in the D III Mechanical Engineering FT UNJ. The criteria used in developing the instrument refer to the criteria used by Centra (1982), in the form of a questionnaire developed based on a Likert scale. Based on the research that has been done, it can be concluded: Student assessment of the purpose of planning and teaching materials for Work Practices by 3.4% stated less, 24.1% were moderate and 41.4 good, and the same opinion of students about lecture practices of welding work practices . So it is recommended that the planning process and the objectives of the welding work practice course need to be revised or improved.